CFRP Strengthening of Pre-damaged Fiber Reinforced Recycled and Lightweight Concrete Beams - AbdelMessih, Michael (2023)
A Master of Science thesis in Civil Engineering by Michael AbdelMessih entitled, “CFRP Strengthening of Pre-damaged Fiber Reinforced Recycled and Lightweight Concrete Beams”, submitted in April 2023. Thesis advisor is Dr. Sherif Yehia. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).